Child sexual abuse by representatives of the Catholic Church: The Chilean case - Contreras Taibo, Lorena; Maffioletti Celedón, Francisco; Pereda Beltrán, Noemí (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
This research aims to describe the characteristics of a group of 21 victims of sexual abuse by a representative of the Catholic Church in Chile. The characteristics of the sexual victimization and the perpetrator, the disclosure and notification, and the experience of other forms of victimization by non-clergy were evaluated. The results show that the abuses began at puberty, included behaviors with physical contact, were committed by men, mainly priests, and were revealed by the victims in adulthood, reported to the Church itself. Most victims also suffered maltreatment by their parents or primary caregivers and sexual abuse by other people, making them poly-victims and underscoring the seriousness of these cases.